The role of substance use in the lives of incarcerated older adults: A qualitative study - Avieli, Hila (Frontiers in Psychiatry, 2023)
Background The prevalence of drug abuse among older adults has grown over the last decade. Despite the expanding development of a body of research dedicated to studying this phenomenon, drug abuse by incarcerated older adults has been marginalized. Thus, the aim of the present study was to explore drug abuse patterns in the lives of incarcerated older adults. Method Semi-structured interviews were conducted with 28 incarcerated older adults, and an interpretive analysis was used to analyze the participants’ narratives. Findings Four themes emerged: (1) Growing up around drugs; (2) Prison onset; (3) Professionals, and (4) Lifelong substance abuse. Conclusion The study findings reveal a unique typology of drug-related themes in the lives of incarcerated older adults. This typology sheds light on the interplay between aging, drug use, and incarceration and the way these three socially marginalized positions may intersect.